ANALYSIS OF EMPLOYEE COMPETENCY DEVELOPMENT IN THE PERSONNEL DIVISION OF THE CENTRAL LAMPUNG REGENCY EDUCATION OFFICE - Yosefin Isnawarah; Malik (International Journal of Multidisciplinary Reseach, 2026)
The research method used was descriptive qualitative research. This method was used to describe the analysis of employee competency development in the Personnel Division of the Central Lampung Regency Education Office. All data were obtained directly from informants in the field using interviews and document studies. The results of the study indicate that employee competency development in the Personnel Division of the Central Lampung Regency Education Office has been implemented through various educational and training activities, but implementation has not been fully optimized. This is evident in the persistent obstacles in the dimensions of employee motivation, personal traits, self-concept, knowledge, and skills. This condition has resulted in less than optimal improvement in professionalism and the quality of employee services.